La Banca Digital y su impacto en los servicios financieros, entidades de la SEPS Segmento 1, Provincia de Chimborazo, período 2022. - Olmedo Caiza, Cristian Daniel (2024)
ABSTRACT: This research entitled "Digital Banking and its impact on financial services, entities of SEPS Segment 1, province of Chimborazo, period 2022", was developed with the purpose of identifying the impact that digital banking has had on financial services. The first chapter focused on the formulation of the problem, establishing the general and specific objectives of the study. In the second chapter, we reviewed the perspectives of several authors that support the research, analyzing the relevant conceptualizations. In the third chapter, we detailed the methodology applied for the execution of the project. The research approach was quantitative, using two types of research: documentary and descriptive, involving surveys of members and interviews with cooperative managers. The research design was non-experimental, not involving manipulation of variables. The population analyzed was 100%. The fourth chapter is the review of documentation of financial services offered by the entities, we collected general information from the cooperatives, we conducted an interview with the managers and we applied a survey to the members of the cooperatives, we analyzed the survey to determine the benefits and challenges that involve the adoption of digital banking. This research represents a systematic effort to understand and manage the impact of digital banking, contributing to the optimization of financial services for Cooperatives. Keywords: Digital Banking, Financial Services, Impact, Adoption. Reviewed by: Msc. Enrique Guambo Yerovi ENGLISH PROFESSOR C.C. 0601802424